Plan estratégico de desarrollo institucional y comercia para el fortalecimiento de la asociación de cafeteros (RAPCIC) - Vera, Diego J. (2018)
This project has as a main objective the elaboration of a strategic plan of institutional and commerce developing with the aim of strengthening the association of “cafeteros” “RAPCIC”, with the objective to solve the different difficulties that the administrative, productive and commercial departments of the associative network have shown due to the lack of an appropriate development on their institutional areas, where, it is not accomplished an optimal performance. It will be determined all the weaknesses of the Association, through a commercial and institutional diagnostic, which was based on the internal and external analysis according to the environment of the organisation, which will allow to increase the strengthens, to take advantage of the opportunities, to perfect the weaknesses and, to compete against the risks where the product and the Association was involved in.